Application of The Local Government Financial Accounting System to The Quality of Local Government Financial Reports at The Kepuharjo Village Office, Karangploso District, Malang Regency - Maria Rosniyati Mbeo; Gunawan, Cakti Indra; Sri Andika Putri (International Journal of Management and Business, 2025)
This research examines various aspects of implementing the Regional Government Financial Accounting System on the Quality of Regional Government Financial Reports at the Kepuharjo Village Office, Karangploso District, Malang Regency. In this study, the independent variable examined is the Implementation of the Regional Government Financial Accounting System, while the dependent variable studied is the quality of financial reports. This research uses a descriptive and verificative analytical approach, using primary data from interviews and observations. This study employs a qualitative method. The results of this study indicate that the implementation of the government financial accounting system at the Kepuharjo Village Office, Karangploso District, Malang Regency, is in accordance with the proposed plan for the execution of various activities that aligns with the Budget Plan (RAB). The quality of the regional government financial reports at the Kepuharjo Village Office, Karangploso District, Malang Regency, is consistent with the budget allocated for implementing both physical and non-physical activities.